Implementation of e-Government via Lapak Aduan Banyumas - Arif Kusuma; Jayanti Armida Sari (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
The purpose of this writing is to assess the community participation in Kabupaten Banyumas in utilizing E-Government media, analyze the supportive and inhibiting factors in the implementation of E-Government, and evaluate the efforts made by the Kabupaten Banyumas Government in overcoming these challenges. This qualitative research involves a literature review. The research process includes gathering primary and secondary literature sources, data processing, citation extraction, and abstraction to present research findings. Interpreting these findings generates comprehensive information, leading to knowledge acquisition for conclusive insights. The results of the discussed research reveal that Lapak Aduan Banyumas is an effective and efficient communication medium between the community and local government through social media, enhancing community participation in politics. Besides, uneven network infrastructure, particularly inadequate transmission towers and fiber optic cables in the hilly areas of Kabupaten Banyumas, results in unsatisfactory website-based service delivery.